NF-E2-related factor 1 suppresses the expression of a spermine oxidase and the production of highly reactive acrolein - Tomoaki Hirakawa; Megumi Taniuchi; Yoko Iguchi; Sudarma Bogahawaththa; Kiko Yoshitake; Shanika Werellagama; Takeshi Uemura; Tadayuki Tsujita (Scientific Reports)
Abstract Polyamines (putrescine, spermidine, and spermine) are among the most abundant intracellular small molecular metabolites, with concentrations at the mM level. The ratios of these three molecules remain constant under physiological conditions. Stress (i.e. polyamine overload, oxidative stress, aging, infection, etc.) triggers the catabolic conversion of spermine to spermidine, ultimately yielding acrolein and hydrogen peroxide. The potential of acrolein to induce DNA damage and protein denaturation is 1,000 times greater than that of reactive oxygen species. We have shown that these polyamine metabolic pathways also involve the nuclear factor erythroid-2-related factor 1 (NRF1) transcription factor. In our chemically-inducible, liver-specific Nrf1-knockout mice, the polyamine catabolic pathway dominated the anabolic pathway, producing free acrolein and accumulating acrolein-conjugated proteins in vivo. This metabolic feature implicates SMOX as an important causative enzyme. Chromatin immunoprecipitation and reporter assays confirmed that NRF1 directly suppressed Smox expression. This effect was also observed in vitro. Ectopic overexpression of SMOX increased the accumulation of free acrolein and acrolein-conjugated proteins. SMOX knockdown reversed the accumulation of free acrolein and acrolein-conjugated proteins. Our results show that NRF1 typically suppresses Smox expression when NRF1 is downregulated, SMOX is upregulated, and polyamine metabolic pathways are altered, producing low molecular weight polyamines and acrolein.